RACISM AS REFLECTED IN THE KITE RUNNER: A CRITICAL READING - M Fakhran Al-Ramadan (English Didactic, 2021)
This study aims at investigating how a fiction text unravels racism and reflects the social structure in real life. The intertwining between fiction and reality makes this a fruitful space to deconstruct the practices of racism as a part of post-colonial activism. The study uses sociology-based literary criticism to deconstruct the portrayal of racism in The Kite Runner. Findings demonstrate that racism as illustrated in the novel can be made visible in pedagogical practices and inspire language learners not to mimic them in their lives.